Ethnicity and obesity: Evidence of implicit work performance stereo-types in Sweden - Jens Agerström; Rickard Carlsson; Dan-Olof Rooth (Institute for Labour Market Policy Evaluation (IFAU), 2007)
Using the Implicit Association Test, we investigate whether employers and students possess implicit and explicit negative attitudes and implicit performance stereotypes toward Arab-Muslim men relative to native Swedish men. We also examine if employers and students have implicit and explicit performance stereotypes toward obese individuals relative to people of normal weight. The results demonstrate that employers and students both implicitly and explicitly associate Arab-Muslim men with less work performance. Also, they have more implicit negative attitudes toward this ethnic group. Obese individuals are both implicitly and explicitly associated with less work performance compared with normal-weight individuals.
Keywords: J53; J64; J71; 330; Implicit; attitudes; stereotypes; discrimination; ethnicity; obesity; Ethnische Gruppe; Gesundheitsrisiko; Personalbeurteilung; Meinung; Schweden